Fixed Point Theory and Chaos - Huerta-Cuellar, Guillermo (IntechOpen, 2023)
The field of mathematics has produced many beautiful results, and among them, fixed points hold great importance as they can be used to describe and explain various mathematical curiosities, even those of the most complex technical applications. This book explores some of the latest and most fascinating results on the study of fixed points from a scientific perspective and presents new approaches to studying them along with possible applications.